Post-Colonial Analysis of Joseph Conrad’s Heart of Darkness - Güven, Samet (Journal of History Culture and Art Research, 2013)
Joseph Conrad’s Heart of Darkness tells the journey of Marlow through the African jungle and his search for the European Kurtz who exploits the natives by imposing violence. It is mainly based upon Conrad’s own experience in Congo. Conrad learned how Europeans exploited and traded the natives for their own benefits during his own journey. The book is regarded as an attack on imperialism and criticizes immoral treatments of the European colonizers in Africa in the 19th century. Keith Booker states that the book deals with issues such as imperialism, capitalism, race, and gender that were very much at the forefront of the turn-of-the century European mind. Conrad’s ambivalent treatment of these issues is extremely representative of the way they were treated in any number of European discourses of the time (217). Besides, Chinua Achebe in his An Image of Africa: Racism in Conrad’s Heart of Darkness comments that Heart of Darkness projects the image of Africa as ’the other world’, the antithesis of Europe and therefore of civilization, a place where man’s vaunted intelligence and refinement are finally mocked by triumphant bestiality (338). Although Achebe puts forward that the novel is in favor of colonialism, I consider that Conrad does not intend to write it to appreciate colonialism and therefore the purpose of this study is to approach Conrad’s Heart of Darkness from post-colonial perspective by taking European imperialism and colonialism over Africa into consideration in order to clarify how Conrad has deconstructed binary oppositions of colonialism by subverting the general idea of the Europeans towards Africa in the 19th century.